Exploring managerial talk through metaphor: An opportunity to bridge rigour and relevance?. Issue 2 (April 2015) - Latusek, Dominika; Vlaar, Paul WL
In this article, we elucidate that exploring managerial talk through the lens of metaphor might offer an opportunity to bridge the often acclaimed gap between rigour and relevance in management research and education. Building on an interpretative research approach and a qualitative field study among managers from the Netherlands, Poland and the United States, we reveal that managers view their day-to-day interactions in relationships with suppliers and clients as if they perform acts, play games and fight battles. These findings corroborate extant research, but they also show that combining (a) the use of metaphor as an analytical tool with (b) a focus on managers' perceptions of their own and others' micro-level behaviours offers substantial potential for synthesising theory with practice. More specifically, we argue that the layered nature of metaphors – on a primary level helping us imbue meaning to raw observations, and on a theoretical level drawing our attention to potentially interesting constructs – propels confrontation and symbiosis between research and practice. Simultaneously, a focus on micro-level behaviours enhances recognisability for practitioners, while facilitating the emergence of fine-mazed patterns underlying emerging constructs on a theoretical level.